2016
DOI: 10.1016/j.jhin.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in faecal microbiota transplant: a review of the literature

Abstract: The vast majority of adverse events of FMT appear to be mild, self-limiting and gastrointestinal in nature. In some cases, a credible association was not established due to the lack of controlled data. There is a need for standardized, randomized controlled trials to qualify and quantify the risks associated with FMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
126
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 110 publications
(351 reference statements)
5
126
0
7
Order By: Relevance
“…Whereas vancomycin only cured 31% of patients, FMT cured 81% of patients after a single infusion and 94% of patients after repeated infusion [105]. Other possible indications for FMT include irritable bowel syndrome, inflammatory bowel disease, constipation, and metabolic syndrome [106].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas vancomycin only cured 31% of patients, FMT cured 81% of patients after a single infusion and 94% of patients after repeated infusion [105]. Other possible indications for FMT include irritable bowel syndrome, inflammatory bowel disease, constipation, and metabolic syndrome [106].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…FMT-related adverse events are rare, generally mild and self-limiting, and mostly constitute gastrointestinal discomfort. Serious adverse events that were reported included bacteremia, perforations, and death and occurred in patients who were severely ill prior to FMT [106].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…1 190 réalisées pour infections à Clostridium difficile [26]. La plupart des effets secondaires observés sont surtout digestifs avec environ 75 % des patients qui présentent des diarrhées et 50 % qui déclarent avoir des douleurs abdominales dans les heures suivant la transplantation fécale.…”
Section: Progrès Techniquesunclassified
“…Un faible nombre de patients disent souffrir de constipation à la suite de la greffe. Les effets secondaires graves comme des bactériémies causées par des entérobactéries, parfois fatales, ou des perforations intestinales, sont rares [26,27]. Deux cas d'infections à norovirus 5 ont été documentés [26].…”
Section: Progrès Techniquesunclassified
“…Th e use of frozen FMT capsules simplifi es administration while obviating any invasive procedures, thus further increasing cost eff ectiveness and safety ( 10,11 ). Two recently published reviews assessing the safety of FMT concluded that most serious adverse events reported were procedure related ( 12,13 ). Storage of frozen capsules is still limited to −80 °C, necessitating on-site administration or cumbersome (and costly) delivery on dry ice.…”
mentioning
confidence: 99%